Lactic acid production by Enteroccocus faecium in liquefied sago starch - Cirilo, Nolasco-Hipolito; Octavio, Carvajal Zarrabal; Rubena, Malfia Kamaldin; Ling, Teck Yee; Samuel, Lihan; Kopli, Bujang; Youji, Nitta (AMB EXPRESS, 2012)
Enterococcus faecium No. 78 (PNCM-BIOTECH 10375) isolated from puto, a type of fermented rice in the Philippines was used to produce lactic acid in repeated batch fermentation mode. Enzymatically liquefied sago starch was used as the sole carbon source, since sago (Metroxylon spp) is a sustainable crop for industrial exploitation. Liquefied sago starch was inoculated with E. faecium to perform the saccharification and fermentation processes simultaneously. Results demonstrated that E. faecium was reused for 11 fermentation cycles with an average lactic acid yield of 36.3 ± 4.71 g/l. The lactic acid production was superior to that of simple batch mode and continuous fermentation in terms of lactic acid concentration. An un-dissociated lactic acid concentration of 1.15 mM affected the productivity of the cells. Work is in progress to maintain and increase the usability of the cells over higher fermentation cycles.